Análisis financiero de una empresa camaronera bajo el sistema de cultivo semi intensivo en la provincia del Guayas - Novillo Torres, Galo Iván (2012)
The studied company was created by a group of investors of El Oro willing to change the schema of traditional shrimp farming. With a different view to what was known at the time of its establishment, is committed to giving priority to other important but which had been ne-glected by other businesses such as infrastructure and quality of life of its employees, as well it invests more time cultivation, to obtain a more marketable size shrimp that barely produced in our country. The market size of this risk is extremely high mortalities due to set out the shrimp in the pond and the high rate of crime afflicting our country today, added to this is the liquidity that the company needs to keep output greater number of days than usual. Partners over the target to get maximum utility, have left the concerns predominate sources of em-ployment and without dodging profitability, have become one of the most important contribu-tions to the community: the creation of sources of employment. With the development of this thesis is expected to get a better view from the financial point of investment with business partners shrimp.